2014
DOI: 10.1128/jvi.00379-14
|View full text |Cite
|
Sign up to set email alerts
|

E1-Mediated Recruitment of a UAF1-USP Deubiquitinase Complex Facilitates Human Papillomavirus DNA Replication

Abstract: The human papillomavirus (HPV) E1 helicase promotes viral DNA replication through its DNA unwinding activity and association with host factors. The E1 proteins from anogenital HPV types interact with the cellular WD repeat-containing factor UAF1 (formerly known as p80). Specific amino acid substitutions in E1 that impair this interaction inhibit maintenance of the viral episome in immortalized keratinocytes and reduce viral DNA replication by up to 70% in transient assays. In this study, we determined by affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
5
34
0
1
Order By: Relevance
“…To test if the stimulatory effect of PUBS described above was dependent on the enzymatic activity of UAF1-containing deubiquitinase complexes, we tested if it could be abrogated by overexpression of catalytically inactive USP1 (USP1ci), USP12ci, and USP46ci. We previously reported that these USPci enzymes inhibit the ability of wild-type E1 to support viral DNA replication by 40 to 70%, while having much less of an effect on the E1⌬ protein (13). The results presented in Fig.…”
Section: Phlpp1supporting
confidence: 50%
See 4 more Smart Citations
“…To test if the stimulatory effect of PUBS described above was dependent on the enzymatic activity of UAF1-containing deubiquitinase complexes, we tested if it could be abrogated by overexpression of catalytically inactive USP1 (USP1ci), USP12ci, and USP46ci. We previously reported that these USPci enzymes inhibit the ability of wild-type E1 to support viral DNA replication by 40 to 70%, while having much less of an effect on the E1⌬ protein (13). The results presented in Fig.…”
Section: Phlpp1supporting
confidence: 50%
“…This HA vector was constructed by substituting the 3F epitope of pCMV3Tag-1a (Stratagene) by an HA epitope. Expression vectors for RFP-USP1, USP12, and USP46 and their catalytically inactive versions were described previously (13). The plasmid used to express the HPV31 E1 UAF1-binding site (UBS) fused to YFP was previously described (referred to as N40-YFP in reference 8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations